A Low-Cost Solution and Continuous Wavelet Transform Analysis for Structural Health Monitoring - Bruno Andò; Danilo Greco; Giacomo Navarra (Proceedings)
In this paper, a low-cost solution for Structural Health Monitoring is proposed, exploiting a dedicated embedded sensing system. Signals provided by the sensor node have been processed by Continuous Wavelet Transform. The node behavior to seismic-like solicitations and has been assessed in the case of frequency sweeps. The results demonstrate the system’s suitability for use in Early Warning frameworks.